2018
DOI: 10.1016/j.exger.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila larvae fed palm fruit juice (PFJ) delay pupation via expression regulation of hormetic stress response genes linked to ageing and longevity

Abstract: Palm fruit juice (PFJ) containing oil palm phenolics is obtained as a by-product from oil palm (Elaeis guineensis) fruit milling. It contains shikimic acid, soluble fibre and various phenolic acids including p-hydroxybenzoic acid and three caffeoylshikimic acid isomers. PFJ has also demonstrated beneficial health properties in various biological models. Increasing concentrations of PFJ and different PFJ fractions were used to assess growth dynamics and possible anti-ageing properties in fruit flies (Drosophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…84 Alteration of hormetic stress response genes with increase in fruit fly longevityFruit FlyLeow et al . 85 Increase in neuroprotection and enhancement of cognitive processesMouseLeow et al . 64 Reduction of plasma lipids and reduced obesity via altered metabolic energy profileMouseSambanthamurthi et al .…”
Section: Introductionmentioning
confidence: 99%
“…84 Alteration of hormetic stress response genes with increase in fruit fly longevityFruit FlyLeow et al . 85 Increase in neuroprotection and enhancement of cognitive processesMouseLeow et al . 64 Reduction of plasma lipids and reduced obesity via altered metabolic energy profileMouseSambanthamurthi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Plant phenols also increase longevity and ameliorate metabolic diseases in insects [ 69 , 70 , 71 ]. Palm fruit juice (PFJ) from Elaeis guineensis contains palm oil phenolics [ 70 , 72 , 73 ] with beneficial health properties including anti-diabetic activity in mammals by slowing glucose absorption, decreasing insulin resistance and/or improving insulin secretion [ 70 , 74 ]. Different concentrations of PFJ and its fractions were used to assess growth dynamics and anti-aging effects in Drosophila [ 70 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…Palm fruit juice (PFJ) from Elaeis guineensis contains palm oil phenolics [ 70 , 72 , 73 ] with beneficial health properties including anti-diabetic activity in mammals by slowing glucose absorption, decreasing insulin resistance and/or improving insulin secretion [ 70 , 74 ]. Different concentrations of PFJ and its fractions were used to assess growth dynamics and anti-aging effects in Drosophila [ 70 ]. The study revealed that PFJ extended the growth stages of larvae and increased the lifespan of adult flies [ 70 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…Eclosed fruit flies fed PFJ or its fractions during the larval stage, then aged on PFJ-free SBD showed 20-40% improved survival ratings over controls. Transcriptomic analysis on whole fruit fly larvae and larval fat bodies revealed that PFJ supplementation generally lengthened the active stage of the fruit fly larvae and this may thus delay their aging process via expression regulation of hormetic stress response genes (Tor, various heat shock proteins, and Sod2) linked to aging and longevity [94].…”
Section: Research 421 Pre-clinicalmentioning
confidence: 99%